The Effect of Special Exercises According to Specific Areas device On Learning low forehand reverse Of Squash Players Aged 13-15 years old - Hadi, Agader; Ramadan, Ali (Journal of Physical Education, 2024)
The research aims to prepare special exercises according to specific areas in the accuracy of performing the reverse low blow for squash players, and to identify the effect of special exercises according to specific areas in the accuracy of performing the reverse low blow for squash players. To achieve the goal, the researchers used the experimental method by designing the experimental and control groups with pre- and post-tests to suit it with the research problem. The research population was chosen intentionally, and they are junior squash players aged (13-15) years, who number (12 junior players), as the research sample constituted (100%). ) From the research community, they were chosen intentionally because there were no other players in the game of squash. After the tests and variables to be studied were determined, the researchers conducted the exploratory experiment as well as the pre-test, and then the exercises were applied during the training units. After completing the training units, the researchers conducted the post-test on the sample, and the researchers used the statistical package (Spss), and the researchers concluded that the exercises The special exercises contributed significantly to increasing the learning rate of the forward reverse low blow. These exercises also contributed to adding an atmosphere of suspense, excitement, and enthusiasm to the research sample, which contributed to breaking the deadlock in diversifying the exercises. The researchers recommend using the exercises prepared by the researcher, and creating exercises that suit the needs and level of The selected sample, and the necessity of conducting similar research on samples from other categories.